2021
DOI: 10.1002/ijgo.13726
|View full text |Cite
|
Sign up to set email alerts
|

Maternal death related to COVID‐19: A systematic review and meta‐analysis focused on maternal co‐morbidities and clinical characteristics

Abstract: Background Besides reducing the quality of obstetric care, the direct impact of COVID‐19 on pregnancy and postpartum is uncertain. Objective To evaluate the characteristics of pregnant women who died due to COVID‐19. Search strategy Cochrane Library, Embase, MEDLINE, Scopus, and Google Scholar were searched from inception to February 2021. Selection criteria Studies that compared deceased and survived pregnant women with COVID‐19. Data collection and analysis Relevant data were extracted and tabulated. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 35 publications
7
37
2
7
Order By: Relevance
“…The present study supports the conclusion of a recent meta-analyses where the authors proved that COVID-19 with at least one co-morbidity increases risk of intensive care and mortality [ 25 ]. However, new insights are showing the promising role of different therapies such as modulators of endocannabinoids receptor and alpha-lipoic acid in the management of COVID-19 related inflammation [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study supports the conclusion of a recent meta-analyses where the authors proved that COVID-19 with at least one co-morbidity increases risk of intensive care and mortality [ 25 ]. However, new insights are showing the promising role of different therapies such as modulators of endocannabinoids receptor and alpha-lipoic acid in the management of COVID-19 related inflammation [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…A recent systematic review has indicated that comorbidities such as obesity (OR 2.48), diabetes (OR 5.7) and asthma (OR 2.02) are significantly associated with maternal mortality 6 . In the present study, comorbidities such as anaemia, tuberculosis and diabetes mellitus were associated with an increased risk of maternal death in pregnant and post-partum women with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Previous respiratory virus outbreaks, including severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome, are associated with increased risk of stillbirth, pre-term birth and foetal growth restriction 2 . In the context of SARS-CoV-2, although initial reports had suggested no detrimental effects of the infection on pregnant women 3 4 5 , large-scale studies and systematic reviews have shown that pregnant women with COVID-19 are at a higher risk for severe disease, abortions and maternal deaths 6 7 8 . A systematic review of available systematic reviews suggests that the risk of maternal death, stillbirth and neonatal death is around one per cent of pregnancies complicated with SARS-CoV-2 infection 9 .…”
mentioning
confidence: 99%
“…Co-morbidities increased the risk of intensive care admission and mortality significantly ( 80 ). In retrospective studies of pregnant women with confirmed or suspected COVID-19, the risk for pneumonia increased with maternal age above 35 years and lymphopenia, whereas it decreased with gestational age ( 76 , 81 ). Surprisingly, high serum liver enzymes and D-dimers did not modify the risk of developing pneumonia ( 59 , 74 , 75 ).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 98%
“…A significant increase in stillbirth, ruptured ectopic pregnancies, maternal depression, and maternal deaths was also reported during the COVID-19 pandemic, but these findings came from studies with “critically low” overall quality due to lack or inconsistency in the selection of healthy controls, unreported or unclear definition of diseases, lack of clarity in reporting of outcomes, study design (e.g., retrospective analysis), and substantial statistical heterogeneity. Additionally, as an indirect consequence of the COVID-19 pandemic, changes in healthcare-seeking behavior and in the access to prenatal services have been reported as impacting negatively on the maternal outcomes ( 81 ).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%